Strategi Koping Dalam Konteks Komunikasi Interpersonal Pada Mahasiswa Dalam Penyusunan Skripsi - Deny D; Raffi A; Elda Putri; Hanif Luqman (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
Thesis writing is a crucial phase in completing undergraduate studies, often accompanied by academic stress and anxiety. This study aims to understand the role of interpersonal communication and coping strategies in overcoming academic anxiety experienced by final-semester students during the thesis writing process. This research focuses on the forms of interpersonal communication between students and their supervisors, peers, and their environment, as well as the coping strategies they use, both adaptive and maladaptive. Using a qualitative approach, this study examines the relationship between the effectiveness of interpersonal communication and the types of coping strategies on students' levels of academic anxiety. The expected outcome of this study is a deeper understanding of effective communication and coping mechanisms in supporting students' academic success. Theoretically, this research is expected to enrich studies in the fields of interpersonal communication, educational psychology, and stress management. Practically, the findings of this study are expected to serve as a reference in designing more supportive academic mentoring programs for students.